(untitled) (Gaceta Técnica, 2025)
The study characterized the main failures in visible structural members of the Dean’s Office of Health Sciences building at the Lisandro Alvarado Centroccidental University in Barquisimeto, in order to determine the mechanism that allowed these failures to develop. A visual inspection of the building was applied. Construction began in 1974. The structure is a reinforced concrete structure with a clean finish, consisting of two levels, and a construction area of 12,744.08 m2 on the ground and upper floors, respectively, and 11,333.81 m2 for the roof. It was determined that the exposure environment is C3, which makes the concrete sensitive to carbonation damage. During the survey of the symptoms of the failures, it was verified that the failure mechanism begins with the roof; the failure of the asphalt layer represents 34,09% of the failures. On the upper floor, efflorescence is 42.34%, and on the ground floor, 64,29%. It is presumed that the main cause of the failures is due to the lack of maintenance that triggered the deterioration, so a plan must be made for the structural, roof, and drainage subsystems, which will contribute to extending the useful life of this important building